Implementation of dental specialty centers: a descriptive analysis of the current status in the Brazilian territory - Estery, Laura; Cericato, Graziela O.; Rigo, Lilian; Rode, Sigmar M. [UNESP]; Lima, Igor F. P.; Paranhos, Luiz R. (Acad Brasileira De Ciencias, 2017)
This study aimed to assess the current implementation status of Dental Specialty Centers (Centros de Especialidades Odontologicas - CEO) in Brazil. The sample included CEOs implemented up to November 2015 in the 27 Brazilian federative units. Data were obtained directly from the database of the Informatics Department of the Brazilian Unified Health System, according to the National Registry of Health Facilities (NRHF) of Dental Specialty Centers of all Brazilian regions. Primary care data were also collected from the cities with implemented CEOs, including coverage status of the Family Health Strategy (FHS) and number of Oral Health Teams (OHT) I and II, at 2 collection periods (January 2006 and November 2015). There were 1019 CEOs implemented in Brazil, which were unequally distributed among the Brazilian states, with prevalence of implementation of CEOs type II (n=503, 49.4%). The statistical analysis showed significant difference between the three types of CEO (I, II, and III) and the variables of coverage rate (FHS) and number of teams (OHT I, OHT II) at both data collection periods. Although presenting an evolutionary aspect in the implementation of CEOs, the implementation of medium-complexity care in Brazil is disorganized.
Keywords: healthcare; secondary healthcare; oral health; policies of dental specialty centers